KOMPONEN HASIL DAN HASIL BERBAGAI VARIETAS TANAMAN PADI (Oryza sativa L.) DAN BAHAN ORGANIK DENGAN METODE SYSTEM OF RICE INTENSIFICATION - Putra Utama; Nurmayulis x; Ikmal x (Jurusan Agroekoteknologi Fakultas Pertanian Untirta, 2014)
This study aims to determine yield componen dan yield of some rice varieties (oryza sativa L.) and organic material with methods system of rice intensification (SRI). This research was conducted in the village of Kaduranca Cibojong Padarincang District of Serang Banten Province, from May 2013 to September 2013 using a factorial randomized block design repeated 3 times. Factors studied included rice varieties, namely: Inpari 11, Ciherang, and HIPA 10 and granting some organic ingredients, namely: Without organic matter, Organic Materials rice straw. The results showed that the use of some varieties showed the best effection the parameters of number of grains perpanicle and grain weight of 1000 grains. HIPA 10 varieties and varieties Ciherang was higher than varieties Inpari 11. While the number offilled grain parameters, the number of empty grains, weightof dry grain harvest, and dry milled grain weight had no significant effect. Provision of straw and organic material gave the best effect on plant height, number of tillers, number of productive tillers, dry weight of harvested grain, milled rice weight, percentage of empty grains and the percentage of filled grain. There was no interaction between several varieties of rice plants with the organic material toall observed variables.